THE PARENTS’ ROLE IN MOTIVATING STUDENTS TO LEARN ENGLISH AS A FOREIGN LANGUAGE AT SCHOOL OF COASTAL AREA IN INDONESIA - Heriyanti Tahang; Seska Paparang; Yuliana Yuliana; Risda Irianti; Syahira Syahira (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2023)
In achieving successful learning in education, parents can be a big trigger that can influence it. Whereas in the coastal area, Parents' involvement in learning language has only been investigated by a few former researchers. While Sorong as a coastal area that has been a transit area for Internasional tourism to Raja Ampat, learning the English Language becomes important. For the reason, the recent research aimed to describe the role of parents to motivate students to learn Language at a school in Sorong as a coastal area. The questionnaire was used to collect the data in a quantitative research design. The data has shown that the parents’ role in motivating students to learn English is showed as enough category with 59.62 scales based on the questionnaires’ answers of 24 Parents in Junior hight school 1 of Sorong. Among the three parents' main roles, the motivator was the role that the most involved by parents in 66 scales in the Good category. The second is as an educator, 58 scales as Enough Category, and the last is as a facilitator, 54.6 scales, in Enough Category. The recent research revealed that the parents' role as motivator, facilitator, and educator in motivation their children to learn English in the Coastal area still need to be improved because it is only at enough category.